TREADING THE SUSTAINABLE DEVELOPMENT CONCEPT: NARRATIVE EXPRESSION OF A STATE-OWNED ENTERPRISE - Alinsari, Natasia; Davianti, Arthik (Fakultas Bisnis Universitas Katolik Widya Mandala Surabaya, 2022)
One idea that focuses on the three pillars of sustainability, the economic, social, and environmental pillars, is sustainable development. The main challenge is achieving the balance of economic, social, and environmental elements. BUMN, as a business unit owned by the Government of Indonesia, has a unique role as an agent of development based on the concept of sustainable development. For a corporation in the mining industry, the task is particularly difficult. The integration of a state-owned company's idea of sustainable development, including actions stated in the disclosures, is investigated in this study. Observational data in this study are narrative disclosures presented in the Company's sustainability report from 2007 to 2018. This study applies qualitative content analysis techniques. The results presented are the initial results of the analysis conducted. The results revealed that as a state-owned company, the Company exhibited the concept of sustainable development as a basis for presenting sustainability reports that showed economic performance, social responsibility, and the environment. Disclosure of environmental and social performance has a larger portion than economic performance. Observation companies prioritize environmental preservation and social aspects, including human rights, labor, product responsibility, and society in carrying out corporate activities.